2022
DOI: 10.3390/app122312471
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study on a Soft X-ray Betatron Radiation Source Realized in the Self-Injection Regime of Laser-Plasma Wakefield Acceleration

Abstract: We present an analysis of the performance of a broadband secondary radiation source based on a high-gradient laser-plasma wakefield electron accelerator. In more detail, we report studies of compact and ultra-short X-ray generation via betatron oscillations in plasma channels. For the specific working point examined in this paper, determined by the needs of other experiments ongoing at the facility, at ∼0.02 Hz operation rate, we have found ≲106 photons emitted per shot (with a fluctuation of 50%) in the soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Recently, there has been much theoretical and experimental interest in the energy conversion efficiency of the radiation mechanisms [31][32][33][34][35][36][37][38][39], as well as their dependence on the laser and target parameters [40][41][42][43]. For example, Pandit et al [40] found that if the laser intensity exceeds ∼ 10 22 W/cm 2 , synchrotron radiation dominates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been much theoretical and experimental interest in the energy conversion efficiency of the radiation mechanisms [31][32][33][34][35][36][37][38][39], as well as their dependence on the laser and target parameters [40][41][42][43]. For example, Pandit et al [40] found that if the laser intensity exceeds ∼ 10 22 W/cm 2 , synchrotron radiation dominates.…”
Section: Introductionmentioning
confidence: 99%